Back to the future in a petri dish: Origin and impact of resurrected microbes in natural populations. (17th October 2017) - Houwenhuyse, Shira; Macke, Emilie; Reyserhove, Lien; Bulteel, Lore; Decaestecker, Ellen
Abstract: Current natural populations face new interactions because of the re‐emergence of ancient microbes and viruses. These risks come from the re‐emergence of pathogens kept in laboratories or from pathogens that are retained in the permafrost, which become available upon thawing due to climate change. We here focus on the effects of such re‐emergence in natural host populations based on evolutionary theory of virulence and long‐term studies, which investigate host–pathogen adaptations. Pathogens tend to be locally and temporally adapted to their co‐occurring hosts, but when pathogens from a different environment or different time enter the host community, the degree to which a new host–pathogen interaction is a threat will depend on the specific genotypic associations, the time lag between the host and the pathogen, and the interactions with native or recent host and pathogen species. Some insights can be obtained from long‐term studies using a resurrection ecology approach. These long‐term studies based on time‐shift experiments are essential to obtain insight into the mechanisms underlying host–pathogen coevolution at several ecological and temporal scales. As past pathogens and their corresponding host(s) can differ in infectivity and susceptibility, strong reciprocal selective pressures can be induced by the pathogen. These strong selective pressures often result in an escalating arms race, but do not necessarily result in increased infectivity over time. Human health can also be impacted by these resurrected pathogens as the majority of emerging infectious diseases are zoonoses, which are infectious diseases originating from animal populations naturally transmitted to humans. The sanitary risk associated with pathogen emergence from different environments (spatial or temporal) depends on a combination of socioeconomic, environmental, and ecological factors that affect the virulence or the pathogenic potential of microbes and their ability to infect susceptible host populations.